Effect of EDTA on the Growth Kinetics and Structural and Optical Properties of KDP Crystal. (26th December 2010) - Rahman, Anisur; Podder, Jiban
Abstract : The solubility of potassium dihydrogen phosphate (KDP) was determined for five different temperatures. Metastable zone width of aqueous solutions of KDP saturated at different temperatures was determined by nucleation method in pure form and adding a well-known chelating agent ethylenediaminetetraacetic acid (0.5 mol% EDTA). The induction periodτ was measured, experiments were performed at selected degrees of supersaturation (C/C * ), and the critical nucleation parameters like interfacial energy (σ ) were calculated, based on the classical theory of nucleation. The structural and optical properties of the grown crystals have been investigated. FTIR analysis has been carried out to characterize the grown crystals. Band gap has been calculated from transmission spectra.